PENELITIAN SUMBER AIR BERSIH BAWAH TANAH DI PULAU FLORES - Edyanto, CB Herman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
One of the most important of human life is water. Water may provide easily in certain areas , however, some parts in the world are still being suffered from the lack of fresh water. In eastern part of Indonesia for example people found the source of water several kilometers from their home and meet their basic need for their life. This research was executed in Flores Island to identify and explore the underground water which might be trapped under the town of Ende.